Culturally specific epistemologies - Solís Fonseca, Gustavo (2012)
In this work we wonder about the possibilities of development of scientific research on cultural grounds, not only in business but above all in epistemological terms, exceeding the narrow framework of a culturally specific conception of science as the West and taking advantage of the diversity of worldviews existing in a space like the Peruvian multicultural.